ASSESSMENT OF THE TROPHIC PROCESSES CONSIDERING DIFFERENT DEPTHS IN A HYPERSALINE LAGOON – ARARUAMA LAGOON –RJ - Trevisan, Cleuza Leatriz; Vicente, Murilo de Carvalho; Pontes, Gabriela Cugler de; Carvalho, Angelo Cezar Borges de; Soares de Mello Guimarães, Teresa Cristina; Medeiros, Hellen; Pontes, Juliana; Wasserman, Julio Cesar (Geochimica Brasiliensis, 2022)
The water quality of the Araruama lagoon has deteriorated at an accelerated pace during the last decades, mainly due to increasing urban occupation. The sewage disposed in the lagoon has increased concentration of nutrients, leading to eutrophication, which may cause episodes of algal blooms and fish mortalities. The objective of this study was to evaluate stratification of the water parameters in a same collection of samples. Water samples of eleven stations along the lagoon were collected at surface, middle and bottom. For each sample, the following parameters were analyzed: Salinity, temperature, pH, Eh, BOD, DO, turbidity, POC, Nitrogen and phosphorus. The hydrodynamic characterization showed that regardless a connection with the ocean, a large part of the lagoon is rather influenced by winds than tides. In general, parameters showed a homogeneous behavior along the water column. The results of DO, BOD confirmed that the lagoon is highly oxygenated. High Phosphorus values, combined with the result of the rates N:P show that P is the limiting factor, promoting elevated primary phytoplanktonic productivity. The concentrations of BOD, Total N and Total P, Chlorophyll-a and Phaeopigments corroborate to it.